Cross-Border Financing by the Industrial Sector Increases Competition in the Domestic Banking Sector - Jayaraman, Sudarshan; Kothari, S. P. (The Accounting Review, 2016)
ABSTRACT We predict that access to cross-border financing by the industrial sector reduces firms' reliance on domestic banks, thereby leading to lower rents for banks and greater competition in the domestic banking sector. We also predict that banks take on more risk to offset these lost rents and remain competitive. Using mandatory adoption of International Financial Reporting Standards (IFRS) to identify variation in cross-border financing, we find evidence consistent with our hypotheses. Additional tests verify that the effects emanate from the demand side (i.e., firms not relying on banks) rather than the supply side (i.e., banks not willing to lend to firms). Overall, we document how competition from overseas financial markets influences the domestic banking sector.